Ekspropriasi dan Perlindungan Hukum Hak atas Tanah untuk Infrastruktur Jalan Tol dalam Hukum Positif - Moh. Riziq (Veteran Law Review, 2025)
The Basic Agrarian Law explains the regulation of land rights, which can be given and owned by other people, either alone, together or legal entities. And according to Law No. 2/2012 and Presidential Regulation No. 65/2006, the government can expropriate (take over) the rights to land acquisition by the state for the public interest, which often causes conflict between the government and the community. This research is conducted with juridical-normative research using a legal approach. The result of the research is that the government and the community can come to a mutual agreement through the process of releasing land rights and providing balanced compensation. The government also seeks to provide legal protection for landowners, both preventive and repressive, with the government and the community deliberating to reach an agreement on the amount of compensation given, and providing consignment and support to people who are willing to have their land used for the state and get tax breaks.